2014
DOI: 10.1093/brain/awu174
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the age at onset in spinocerebellar ataxia by CAG tracts in various genes

Abstract: Polyglutamine-coding (CAG)n repeat expansions in seven different genes cause spinocerebellar ataxias. Although the size of the expansion is negatively correlated with age at onset, it accounts for only 50-70% of its variability. To find other factors involved in this variability, we performed a regression analysis in 1255 affected individuals with identified expansions (spinocerebellar ataxia types 1, 2, 3, 6 and 7), recruited through the European Consortium on Spinocerebellar Ataxias, to determine whether age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
150
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 153 publications
(167 citation statements)
references
References 37 publications
14
150
3
Order By: Relevance
“…Choice of statistical modelling might further evidence how populational differences in CAGexp can impact AO determination. Significant increase in explanation of AO variability was detected in Han Chinese,8 European carriers from non-Portuguese populations and Americans6 using quadratic models. Here, the quadratic modelling of CAGexp from IPDs yielded only a marginal improvement when compared with a simpler, linear regression modelling of AO variance.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Choice of statistical modelling might further evidence how populational differences in CAGexp can impact AO determination. Significant increase in explanation of AO variability was detected in Han Chinese,8 European carriers from non-Portuguese populations and Americans6 using quadratic models. Here, the quadratic modelling of CAGexp from IPDs yielded only a marginal improvement when compared with a simpler, linear regression modelling of AO variance.…”
Section: Discussionmentioning
confidence: 93%
“…IPD and AD retrieved from 11 studies comprised four cohorts from Europe,6 7 17 18 three from Asia,8 19 20 one from North America,6 one from Central America21 and three from Brazil 5 22 23. Brazilian cohorts comprised the Rio Grande do Sul (Brazil-RS) cohort23 and cohorts from other Brazilian regions (Brazil-non-RS cohorts): namely, subjects from São Paulo State22 and those described by Neurogenetics Network, a consortium of Brazilian researchers 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Genetic Modifiers of Huntington's Disease (GeM‐HD) genome‐wide association study (GWAS)6 found two genome‐wide loci associated with age at motor onset in HD on chromosomes 15 and 8, with two independent signals at the same locus on chromosome 15. A few SCA genetic modifiers have been proposed3, 5, 7, 8, 9 and no GWAS have been reported.…”
mentioning
confidence: 99%
“…In SCAs with (CAG)n-repeats, the negative correlation between the size of the polyglutamine expansion and the age at onset [56] only accounts for 50-70 % of its variability. A large cohort study on 1255 affected patients allowed an assessment to be made of the influence on the age at onset of the length of the normal allele in trans (SCA1, 6, 7) and of other (CAG)n-containing genes [57]. Furthermore, intermediate-size CAG repeats in ATXN2 were recently shown to be a risk factor in other neurodegenerative diseases, such as amyotrophic lateral sclerosis (ALS), frontotemporal dementia with ALS ([29 repeats [58]), and possibly in Parkinson's disease ([24 repeats [59]).…”
Section: Starting To Uncover the Genes Underlying Phenotypic Heterogementioning
confidence: 99%